Optimizing Incentives for Civil Servants in Cirebon Local Government - Utami, Miranti Pradipta; Suryani, Rani; Aisyah, Nurul; Jusri; Sijabat, Saut Gracer (SAFE-Network, 2023)
This study explores the factors influencing the provision of incentives for civil servants in the Cirebon Local Government. The research adopts a quantitative research design and utilizes survey questionnaires to collect data from a representative sample of 121 civil servants. The variables examined in the study include organizational justice, competence, and leadership effectiveness. The findings indicate that organizational justice significantly influences the provision of incentives, highlighting the importance of a fair and equitable work environment. Competence also emerges as a crucial factor, emphasizing the need for employees to possess the necessary skills and abilities to excel in their roles. Furthermore, effective leadership is found to have a positive impact on incentive provision, underscoring the significance of capable and motivating leaders. The results of this study contribute to the understanding of incentive systems in the Cirebon Local Government and provide insights for policymakers and human resource managers. By considering the factors of organizational justice, competence, and leadership effectiveness, the government can design and implement effective incentive programs that enhance employee motivation, satisfaction, and performance.